The science of medical technology : from humble syringes to lifesaving robots - Senker, Cath; Affonso, Alexandre; Beach, Bryan (2019)
"Introduces the reader to the science of medical technology."--
What is diagnosis -- How do machines save lives? -- Which machines are used for operations? -- How are robots used in surgery? -- Which machines are fixed to your body? -- What are prosthetics? -- What are vaccines? -- Which vaccines are common? -- Will we always need injections? -- Which gadgets can check my health? -- How do we cope with health images? -- How can I stay fit and healthy?.
"Published in Great Britain in 2019 by Book House, an imprint of The Salariya Book Company Ltd."
Includes index.
Ages 7+
Keywords: Medical technology -- Juvenile literature; Medical innovations -- Juvenile literature